Book Review: Quality Assurance and University Rankings in Higher Education in the Asia Pacific: Challenges for Universities and Nations - Abdul Manan, Shakila (Penerbit Universiti Sains Malaysia (USM Press), 2015)
In this increasingly borderless world, student enrolment in colleges, public and private universities have grown exponentially. Although this is a good sign, it has also raised concerns about the quality of teaching practices in higher education; the assessment of tertiary institutions; equity and access to higher education and the issue of international rankings and accreditation. Quality control has become a pressing concern more so now because of the transnational character of higher education. In view of this, since the 1990s, most countries have developed their own "quality assurance mechanisms," many of which were modelled after the Northern countries. However, the adoption of such mechanisms is not without problems, especially for countries in the South, as there are significant "socio-historical, economic, cultural and intra-nation power differentials" between them (BlancoRamirez and Berger 2013).